Maize in 2034: A Decade of Growth, Innovation, and Sustainability in Crop Production - Shah, Ali; Latif, Abdul; Ali, Raja Ahmad; Aiman, Bareeza; Malik, Javeria; Haseeb Ullah; Rizwan, Muhammad Hassan; Haseebullah; Rehman, Hanzala (Indus Journal of Bioscience Research, 2025)
Maize (Zea mays L.) is a major world cereal grain and an important food, feed and raw material crop. This review looks at the changing role of maize in the world’s agriculture, but with an emphasis on the challenges and opportunities that it will likely face in the future. Increased demand for maize (due to population growth, dietary change and expansion of bioenergy production) requires intensified effort to boost productivity while maintaining sustainability and resilience. Increased drought, heat stress, and outbreaks of pests all threaten maize production, and especially in vulnerable regions, climate change is largely seen as an issue. Yet advances in genomics, biotechnology and agronomy hold promise to erase these constraints. These traits are crucial for stabilizing yields: stress tolerant and nutrient efficient maize varieties; precision agriculture and integrated pest management. Crop’s future is also shaped by socioeconomic factors such as technology access, infrastructure development and favourable policy frameworks. Therefore, this review points to the need to focus on the inclusive innovation and equitable distribution of agricultural resources for smallholder farmers in developing countries. It also underscores the importance of environmentally sound maize systems for their long term viability. This review synthesizes current knowledge and identifies strategic priorities by which researchers, policymakers and other stakeholders can improve the contribution of maize to global food systems. Scientific progress alone will not ensure the future of maize; rather it is a matter of collective action towards sustainability, equity, and resilience in agricultural development.